DERMATOGLYPHICS PROFILE OF STREET RUNNERS (Fiep Bulletin - online, 2026)
Introduction: Street running is an easily accessible and popular sporting activity, with a variety of events depending on the distance covered, but the predominance of good aerobic endurance is notable. Dermatoglyphics, a scientific method capable of identifying genetic predispositions for basic physical qualities, is used to analyze and guide a more reliable athletic profile, boosting performance. Objective: To analyze the dermatoglyphic profile of street racers. Methods: The participants were 30 street runners from the Paraiba hinterland who trained regularly and/or had completed endurance races of at least 5 km. A DERMALOG Z2F biometric scanner and VeriFinger 13.1 Fingers Algorithm Demo software were used, following the Cummins and Midlo Protocol (1942), adapted to capture 2 images per fingerprint. The results were analyzed using Microsoft Excel 2020 for Windows and Jamovi Software 2.6.13. Results: There was a prevalence of loop designs, with LU= 2.53±1.46 and LR= 3.03±1.54 (55.67%); the others were W= 2.37±2.31 (23.67%) and A= 2.07±2.94 (20.67%). The index of D10= 10.3±4.6 and SQTL= 99.1±50.6. Predominant digital formula: (A+L)>W= 53.33%. Conclusion: It can be concluded from the analysis that the dermatoglyphic profile of these athletes correlates with the sport, with an increase in SQTL and D10, and in the L and W designs.Keywords: Dermatoglyphics, Running, Athletes.